Lattice Boltzmann investigation of flow boiling in a microchannel. (June 2023) - Wang, He; Wu, Suchen; Dai, Hanhui; Liu, Xiangdong; Zhang, Chengbin
A hybrid multiphase lattice Boltzmann model is adopted to investigate the flow boiling heat transfer process in a horizontal microchannel with consideration of bubble dynamics. The flow pattern transition in a microchannel, involving single-phase flow, bubbly flow, slug flow, and contact-slug flow, is reproduced by varying the heat flux. The influencing parameters, including the liquid mass flux, the heating wall wettability, and the confinement height of channels, on dynamic bubble behaviors and heat transfer performance are discussed. The results indicate that a sequence of single-phase flow, bubbly flow, slug flow, and contact-slug flow occurs in a microchannel with increasing heat flux. Correspondingly, the dominant heat transfer mechanism experiences the liquid convection (single-phase flow), nucleate boiling (bubbly flow), the microlayer evaporation (slug flow), and the hybrid gas convection and microlayer evaporation (contact-slug flow). The increase of mass flux or confinement height extends the range of heat flux for high-efficiency bubbly and slug flow. The hydrophilic heating wall is preferred for better heat transfer performance in a microchannel due to the strengthened microlayer evaporation and less vapor occupation of the effective nucleation area.